Pendekatan Physical Evidence untuk Optimalisasi Pelanggan UMKM Makanan dan Minuman - I Ketut Satria Wisesa; Ni Luh Putu Sariani; Anak Agung Ngurah Oka Suryadinatha Gorda (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
This community service program is intended to determine the effectiveness of applying physical evidence to benefit consumer experience. The observation subjects were MSMEs doing business in the food and beverages (FB) sector in Denpasar City, Bali, Indonesia. The implementation method used by the service team was outreach to business people according to marketing mix theory using the Participatory Action Research (PAR) technique which includes document analysis, webinars, and interviews. The results of this service program showed that the design of communicative physical evidence, in general, can increase the intention to return, which is indicated by an increase in the consumer experience. This activity sparked the emergence of awareness among business actors regarding the importance of implementing the marketing mix.